Adsorption of arsenic and heavy metals from solutions by modified iron ore sludge - Bien, Nguyen Quoc; Ha, Nguyen Thi Hoang (Vietnam Journal of Earth Sciences, 2019)
Water pollution with arsenic (As) and heavy metals has been a major considering issue because of their negative impact on ecosystems and human health. This study was conducted to evaluate the adsorption behavior of As and heavy metals by iron ore sludge modified by the addition of 10% sodium silicate solution and heating at 400°C (SBC2-400-10S) in both batches and fixed–bed column experiments. The kinetics showed that the removal of As and heavy metals by the adsorbent is a pseudo-second-order reaction. The adsorption data fitted well with Langmuir isotherm and provided Langmuir monolayer capacity (mg/g) of As and heavy metals in the following order: Pb (2.379) > Cd (2.008) > Zn (1.915) > Mn (1.692) > As (0.452). The column adsorption data were fairly well described by Thomas model, with the order of Thomas adsorption capacity following a similar trend as in the batch study. The results of this study indicated that SBC2-400-10S was a potential adsorbent for removal of As and heavy metals from solutions.